Legal Force Of The Preliminary Sales Agreement (PPJB) As Evidence For The Seller Againts The Buyer Who Is In Breach Of Contract (Case Study: Decision Of The Surabaya District Court No.862/Pdt.G/2021/Pn Sby. - Trasaenda, Resfa Klarita; Winanti, Atik (Journal of Law, Politic and Humanities, 2025)
This study discusses the legal force of the Sale and Purchase Agreement (PPJB) as evidence for sellers against buyers who commit breach of contract, based on a study of Surabaya District Court Decision Number 862/Pdt.G/2021/PN Sby. This study is based on the prevalence of breach of contract cases in land sale and purchase agreements, which cause legal uncertainty for the parties involved. The main issue in this study is the legal force of a Sale and Purchase Agreement as evidence in Indonesian civil disputes. The purpose of this study is to understand the legal force of a Sale and Purchase Agreement (PPJB) as evidence in civil disputes and to analyze the judge's considerations in Surabaya District Court Decision Number 862/Pdt.G/2021/PN Sby. The research method used is normative juridical with a statute approach and case approach through literature study. The results show that the PPJB has legal force as authentic evidence and that its cancellation must be carried out through a court decision. The judge's considerations in this case are deemed inappropriate because they state that there is a defect of will, whereas both parties agreed on their own will.